Direct contact membrane distillation for liquid desiccant regeneration and fresh water production: Experimental investigation, response surface modeling and optimization. (5th February 2021) - Liu, Jingjing; Ren, Haoshan; Hai, Faisal I.; Albdoor, Ahmed K.; Ma, Zhenjun
Highlights: Membrane distillation was used for desiccant regeneration and water production. Interactions of operating parameters on regeneration performance were evaluated. Transmembrane temperature difference should be maintained higher than a threshold. An optimal flow rate can improve the regeneration performance. Optimal conditions to maximize the regeneration performance were identified. Abstract: Liquid desiccant cooling (LDC) systems are being widely considered as a promising alternative for energy savings and the regeneration is one of the most significant processes of the LDC systems. This paper presents a direct contact membrane distillation (DCMD) regenerator for liquid desiccants regeneration of LDC systems and fresh water production simultaneously. The novelty of this study is to use the response surface method to establish models to predict the DCMD regeneration performance with highly concentrated lithium chloride solutions based on the experimental investigation. The interactive effects of the operating parameters, i.e. initial feed concentration, feed inlet temperature, distillate inlet temperature, and feed and distillate flow rates were studied and the optimal conditions of the DCMD regenerator to maximize the feed concentration increase and transmembrane water flux were identified. The experimental results showed that stable regeneration performance and water production with the lithium chloride salt rejection rate over 99.99% by the membrane were achieved using the DCMD regenerator. The temperature difference between the feed and distillate sides should be controlled higher than a threshold to ensure continuous liquid desiccant regeneration. Initial feed concentration and flow rate exhibited a significant interaction in improving the DCMD regeneration performance. An optimal flow rate for better regeneration performance can be observed when increasing the initial feed concentration. The optimization results showed that the feed concentration increase and transmembrane water flux can be improved by 39.7% and 41.6% respectively under the optimal conditions as compared to the best case observed in the response surface method designed experiments.